Does foreign board increase the company’s performance? the evidence from Indonesia - Muhammad Zhafran Joenoes; Rofikoh Rokhim (Journal of Economics, Business, and Accountancy Ventura, 2019)
This study examined the effect of foreign board members in promoting corporate governance and performance. This study used the fixed effect model from the panel data of 4,282 company-observations over the period of 2007-2017. This study found that the presence of foreign board has a significant and positive effect on the company’s performance measured by return on asset and return on equity ratios. On the other hand, the presence of Asian nationality board member was found to have negative significant effect on the company’s performance, and this is due to the companies having Asian Board members coming mostly from developing countries. In general, this research show that the presence of a foreign board member can bring differences to the companies and this affects their performance. This means that companies in Indonesia need to increase the number of foreign board of commissioners from outside Asian countries in order to increase their profitability.